강활추출물이 OVA-induced Asthma Mouse Model의 면역조절에 미치는 영향 - 유지현; Ji Hyun Yoo; 배진현; Jin Hyun Bae; 도은수; Eun Soo Doh; 장준복; Jun Pok Chang; 성낙술; Nak Sul Seong; 길기정; Ki Jung Kil (大韓本草學會誌, 2011)
Objectives: The aim of this study was to investigate the asthma-suppressive and immuno-regulatory effect of Notopterygii Rhizoma(NR) extract on OVA(ovalbumin)-induced asthma in mice. Methods: C57BL/6 mice out of all the experimental groups, except the Normal group and the NRⅠgroup, were sensitized and challenged with OVA. C57BL/6 mice were exposed to OVA three times a week for 12 weeks and analyzed by flow cytometer, ELISA, H&E stain. Results: The concentrations of IL-4, IL-5, IL-13, IgE in serum of the OVA-NRⅡgroup decreased significantly compared with those of the OVA-Control group. The number of Gr-1+/CD11b+, CCR3+, CD3+/ CD19+, CD3e+/CD69+cells in the OVA-NRⅠ group decreased significantly compared with those of the OVA-Control group. The collagen accumulation in the lung sections of the OVA-NRⅡ group decredased signi- ficantly compared with that of the OVA-Control group. Conclusions: These results suggest that Notopterygii Rhizoma(NR) would be a effective candidate for herbal-originated anti-asthmatic drug. However, this drug should be further studied for characterization of the accurate action and underlying mechanism using variant disease model in the future.